2022
DOI: 10.1080/13880209.2022.2032208
|View full text |Cite
|
Sign up to set email alerts
|

Response surface optimization of enzymatic hydrolysis and ROS scavenging activity of silk sericin hydrolysates

Abstract: Context Sericin, a protein found in wastewater from the silk industry, was shown to contain a variety of biological activities, including antioxidant. The enzymatic conditions have been continuously modified to improve antioxidant effect and scavenging capacity against various free radicals of silk sericin protein. Objective Variables in enzymatic reactions, including pH, temperature and enzyme/substrate ratio were analysed to discover the optimum conditions for antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Thus, for wound healing patches it was essential to include them as proof of the regeneration processes of the skin. Finally, numerous reports have shown that both melatonin and sericin but also resveratrol and turmeric exhibit high antioxidant potential [262][263][264][265]. The elevating secretion of pro-inflammatory cytokines, increased cell proliferation and oxidation processes can damage cell membrane integrity and lead to DNA fragmentation [7,27].…”
Section: Discussion: Melatonin/sericin Collagen Scaffolds As Possible...mentioning
confidence: 99%
“…Thus, for wound healing patches it was essential to include them as proof of the regeneration processes of the skin. Finally, numerous reports have shown that both melatonin and sericin but also resveratrol and turmeric exhibit high antioxidant potential [262][263][264][265]. The elevating secretion of pro-inflammatory cytokines, increased cell proliferation and oxidation processes can damage cell membrane integrity and lead to DNA fragmentation [7,27].…”
Section: Discussion: Melatonin/sericin Collagen Scaffolds As Possible...mentioning
confidence: 99%
“…Hemicelluloses and celluloses are degraded to sugar monomers by enzymatic hydrolysis. The enzymolysis effects are related to enzyme dosage, time, and solid-to-liquid ratio. , …”
Section: Introductionmentioning
confidence: 99%